Aspek Ideational, Interpersonal, Social, dan Textual dalam Pembelajaran Pendidikan Agama Islam - Ismail (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
The teacher is the key to the success of an educational institution. The good or bad behavior or teaching methods of teachers will greatly affect the image of educational institutions. the focus of this study rests on the ideational, interpersonal, social, and textual aspects of Islamic Education Learning. This research uses "Library Research". The research data used is secondary data. The data collection technique used by the authors in this study is documentation. Data processing is carried out by conducting study activities, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. While data analysis uses descriptive-critical-comparative method, and content analysis method. The results of the discussion can be summarized as follows: 1) The ideational aspects of teaching include the 'approach' or ideal methodology 2. With self-emotion, self-control and teacher performance, inner beauty of the teacher becomes a personal reflection that is closely embedded in each step. 3) At least social skills include abilities: Communicating verbally, writing and or polite gestures. Mastering functional communication and information technology. Associate effectively with students, fellow educators, educational staff, leaders of educational units, parents / guardians of students. Hang out politely with the surrounding community by heeding the prevailing norms and value system: and applying the principle of true brotherhood and a spirit of togetherness. 4) Teachers provide varied activities so that they can serve individual student differences; more activating students and teachers; encourage the development of new abilities; and creating a network of learning activities in schools, homes, and community environments